1975
DOI: 10.1136/gut.16.2.118
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of lipid loss from the small intestinal mucosa.

Abstract: SUMMARY Many water-soluble compounds have been shown to pass from the small intestinal mucosa into the lumen. In this work, the loss of lipids from the mucosa was investigated by perfusion experiments in rats, using 0 15M NaCl or buffer solutions over a range of pH, with or without the addition of 5 7 or 11'4 mM taurocholic acid. Perfusates were extracted for the estimation of individual lipids and for DNA, which is a measure of cell loss.The results suggest that free fatty acids reach the lumen by diffusion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The finding of both the FAs and their carnitine esters suggest that they originated from lipids incorporated into host cells, likely hepatocytes or intestinal epithelial cells, and were then secreted in bile or sloughed into the gut lumen, respectively. Even during fasting or on a lipid-free diet, significant amounts of lipids are excreted in feces (56). This is consistent with our previous finding that the body tissue FA composition is strongly influenced by the FA composition of administered parenteral lipid emulsion (26).…”
Section: Discussionsupporting
confidence: 92%
“…The finding of both the FAs and their carnitine esters suggest that they originated from lipids incorporated into host cells, likely hepatocytes or intestinal epithelial cells, and were then secreted in bile or sloughed into the gut lumen, respectively. Even during fasting or on a lipid-free diet, significant amounts of lipids are excreted in feces (56). This is consistent with our previous finding that the body tissue FA composition is strongly influenced by the FA composition of administered parenteral lipid emulsion (26).…”
Section: Discussionsupporting
confidence: 92%
“…The lysophosphatidylcholines were either completely hydrolysed or acylated to form new phosphatidylcholine molecules, while the unsaturated fatty acids were used for triglyceride synthesis. These (Clément et a/., 1955 ;Raulin et Lefort, 1960 ;Clément, 1961 ;Di Costanzo et Waldram, 1975 ;Reisser, 1978) ; chez le Mouton (Zamytchkina et Grodsensky, 1955 (Hauton et Laurent 1965 ;Lairon et al, 1972 ;Nalbone et al, 1973Nalbone et al, , 1978Nalbone et al, , 1979 (Nalbone et al, 1978Vigne et al, 1979Vigne et al, , 1981. L'existence de ce complexe est compatible avec la théorie de l'organisation micellaire des constituants biliaires.…”
mentioning
confidence: 99%
“…Although these data support our hypothesis, it remains to be seen whether in testinal cholesterol comes only from cell sloughing or whether additional cholesterol ex changes occur between cells and lumen. Using 30-min perfusions in rat intestine, Cotton (10) and then Waldram (26) concluded that trigly cerides. cholesterol and phospholipids are lost only by desquamated mucosal cells.…”
Section: Effect O F Thyroxinementioning
confidence: 99%